Padronização de um ELISA indireto para o diagnóstico da imunodeficiência felina a vírus - Fabiana Alves (2010)
Feline immunodeficiency virus (FIV) is a lentivirus that infects felids. FIV infection leads to a chronic disease and immunodeficiency. Clinical diagnosis is not reliable, which makes laboratory diagnosis necessary. The aim of this study was to establish and standardize an indirect ELISA for diagnosis of FIV, using a capsid protein p24 recombinant antigen (r-p24). Additionally, the occurrence of FIV infection in the Belo Horizonte metropolitan area was studied using PCR and immunochromatography SNAP Combo Plus. Conflicting results between both tests were confirmed by Western blot using the r-p24. Serum samples from 150 cats were used: 78 from asymptomatic cats belonging to private owners and from shelters of Belo Horizonte metropolitan area, Minas Gerais, and additional 72 samples donated by Veterinary Clinic Department of Universidade de São Paulo (USP), SP, previously tested by SNAP Combo Plus and PCR. For the of amplification 244 base pars (bp) fragment of the FIV gag gene the oligonucleotide primers were designed. The r-p24 (3.14 g/cm = 0.095 g/animal) was used for the Western blot. The indirect ELISA was standardized using 2.5 ng/ml of r-p24, 1:320 serum dilution and conjugate diluted 1:7500 (anti-feline IgG peroxidase). The r-p24 ELISA showed a 97% sensitivity and 93% specificity when compared to the gold test SNAP Combo Plus, with a Kappa index of 0.83. For the FIV occurrence study in Belo Horizonte, three animals (3.85%) were positive, showing that infected asymptomatic cats can disseminate the virus. Our results indicate that r-p24 ELISA is a sensitive, specific, and simple technique for FIV routine diagnosis and research.